(3GdJMdjd GdLRFjs - (3MQHj eMeO ehSi(B, (3YQjbGJs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2005)
(3eaGgje CSGSjI aj Yde GdEbJUGO(B- (3fXQjGJ GdbjeI(B- (3fXQjI GdWdH(B- (3fXQjI GdYQV(B- (3JhGRf GdWdH hGdYQV(B- (3fXQjI Sdhc GdeSJgdc(B- (3fXQjI GdEfJGL(B- (3fXQjI JcGdja GdEfJGL(B- (3fXQjI GdJhRjY(B- (3fXQjI GdGShGb(B- (3JhGRf GdefJL aj MGdGJ GdGShGb GdeNJdaIs
Keywords: (3GdEbJUGOs; (3GdJMdjd GdEbJUGOjs